Induction of apoptosis in SSN-1cells by Snakehead Fish Vesiculovirus (SHVV) via Matrix protein dependent intrinsic pathway. Issue 113 (June 2021) - Hegazy, Abeer M.; Chen, Nan; Lin, Hanzuo; Babu V., Sarath; Li, Feng; Yang, Youcheng; Qin, Zhendong; Shi, Fei; Li, Jun; Lin, Li
Abstract: An increasing important area in immunology is the process cell death mechanism, enabling the immune system triggered thru extrinsic or intrinsic signals to effectively remove unwanted or virus infected cells called apoptosis. A recently isolated infectious Snakehead fish vesiculovirus (SHVV), comprising negative strand RNA and encoded viral matrix (M) proteins, is responsible for causing cytopathic effects in infected fish cells. However, the mechanism by which viral M protein mediates apoptosis has not been elucidated. Therefore, in the present experiments, it was investigated the regulatory potential of apoptosis signals during SHVV infection. By employing the model of SHVV infection in SSN-1 cells, the accelerated apoptosis pathway involves an intrinsic pathway requiring the activation of caspase-9 but not caspase-3 or -8. In the groups of infection (SHVV) or treatment (hydrogen peroxide) were induced apoptotic morphological changes and indicated the activation of the main caspases, i.e.; executioner caspase-3, initiators caspase-8 and caspase-9 using colorimetric assays. Turning to the role of viral M protein when it was overexpressed in SSN-1 cells, it was indicated that the viral M gene alone has the ability to induce apoptosis. To elucidate the mechanism of apoptosis in SSN-1 cells, the activation inhibitors of main caspases were used showing that inhibiting of caspase-3 or caspase-8 activation did not seize induction of apoptosis in virus-infected SSN-1 cells. However, the inhibiting of caspase-9 activation reduced significantly the apoptosis initiation process and sharply the expression of viral M gene, suggesting that SHVV plays a major role in the early induction of apoptosis by caspase-9. Interestingly, there were also differences in the mitochondrial membrane potential after the apoptotic induction of caspases, which confirm that caspase-9 is primarily responsible for the cleavage of caspases during apoptosis. Taken together, these findings can therefore be assumed that viral M protein induces apoptosis via the intrinsic apoptotic pathway in SHVV infecting SSN-1 cells. Highlights: In SSN-1 cells, caspase-9 is primarily responsible in the intrinsic pathway during SHVV infection. Inhibiting of caspase-9 activation suppresses the apoptosis process. The viral Matrix protein has a role in the apoptotic process. Caspase-9 can affect the expression of viral matrix protein.